How does information and communication technology (ICT) affect oil palm agricultural practices? - Tan, Say Peng; Novel Lyndon; Humaira Ma Taib; Nur Hana Basaruddin; Zaki Aman; Sinyee Gan; Zurinah Tahir (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the factors influencing the adoption of Information and Communication Technology (ICT) among oil palm-independent smallholders and assesses their perception of the use of ICT in agricultural practices. Through personal interviews with 384 independent smallholders, this research examines the relationship between respondents' demographic characteristics and smartphone usage, identifies the factors influencing ICT adoption among oil palm independent smallholders (ISH), and evaluates the extent of ICT usage perceived by ISH. The analysis of the Chi-square test showed a significant difference p<0.05 between the education status of farmers and their use of smartphone brands, the time spent on social media, and the experience with the smartphone. The findings reveal a widespread agreement among smallholders on the value of smartphones, reflecting their recognition of the importance of ICT. However, the study highlights that accessibility to ICT facilities emerged as a significant factor with the lowest mean score, indicating a lack of adequate infrastructure in the surveyed areas. Furthermore, respondents expressed dissatisfaction with the current state of ICT facilities. Conversely, most respondents emphasized the significance of accessing online information on fresh fruit bunch (FFB) prices and demonstrated an eagerness to obtain agricultural information online. This study also emphasizes the need to understand the factors driving ICT adoption among ISH and underscores the importance of enhancing accessibility to ICT facilities and improving satisfaction with existing infrastructure. Empowering ISH to leverage ICT tools effectively can enable them to access vital information and establish efficient connections with potential markets in the digital era. Smartphones as ICT tools have revolutionized the agricultural sector by improving access to information, financial services, and advanced farming tools, thereby fostering higher efficiency and sustainability in agricultural practices.